Asociación de un inmunógeno con un acaricida químico en el control de garrapatas en bovinos en la provincia Pichincha - Rodríguez Armijos, Jaime Alexander (2022)
In the research developed "Association of an immunogen with a chemical acaricide in the control of ticks in cattle in the Pichincha province", the following objectives were set; establish the prevalence of adult ticks present in bovines; verify the decrease in ticks after the association of an immunogen with a chemical acaricide; taxonomically identify the main species of ticks present in the farms and; determine the infestation according to the coloration of the coat and anatomical zone of the bovines under study. In the methodological framework, the experimental material was included, which was 80 bovines, Gavac immunogen and chemical acaricides. Laboratory methods for taxonomic classification and field methods for counting ticks were also carried out. The main results obtained were what; the overall average prevalence of ectoparasites was recorded at 97.5% of the total population. In the initial tick count, there was a general average of 67 mites/bovine; while at the end of the trial 23 ticks/bovine were quantified. The best response in relation to the reduction in the number of ectoparasites over time was determined in the combination of the immunogen (GAVAC ™) in a dose of 2 ml + spray bath every 15 days with Amitraz in a dose of 20ml/20 liters of water A single species of ectoparasites (Rhipicephalus microplus) was identified. The anatomical area of cattle with the highest prevalence of ticks was the hind limbs. There was a predisposition of greater infestation in the dark color.